STREET OFFICE: A BIBLIOGRAPHICAL ANALYSIS OF THE TROUBLES FOR THE EFFECTIVENESS OF CARE - Magdiel Bandeira Montenegro, Felipe; Costa Maia Monteiro, Vinícius; Rayssa Costa Gonçalves Morais, Ana; Machado de Aguiar Cunha, Vânia; Felix da Silva, Josivan; Roseli Silva de Carvalho, Katiucia; Camanducaio Sales Leite, Fernando; Dyego de Morais Torres, Arthur; Hemilia Melo de Medeiros, Maria; Raissa Ferreira da Silva, Herika; Hélio de Souza, Cícero; Aser Veloso Costa, Daniel (Health and Society, 2023)
Introduction: The homeless population, is one of the groups of society that contains the greatest vulnerabilities existing in the current times, they are a heterogeneous group of extreme poverty, without housing, without income and many times without opportunity of education in all your life. This population constantly suffers from violations and prejudices of today’s society, contributing even more to their social exclusion and difficulty in seeking health in public institutions, thus emerging the street clinic to serve them directly in the inserted territory. Objective: To highlight the obstacles to the implementation of street practice assistance in the Brazilian health system. Methodology: The research method used in this research is the integrative literature review, which through research in the virtual health library (VHL) managed to survey 15 articles to build the synthesis of knowledge on top of the axes on the characterization of homeless population, the difficulties for implementing the street clinic in the Brazilian health system and the street clinic as a health strategy for the homeless population. Results and discussion: The homeless population faces daily episodes of social exclusion and vulnerability due to their characteristics that make them live on the streets, such as drug or alcohol addiction, abandonment, mental problems, etc. The episodes suffered by PSR make individuals try to be invisible to the public eye, thus also making it difficult to carry out and assist the street clinic. The strategy of the street office was created in 2011 to meet the demands of the homeless, who in turn face problems when assisting this population, as strategies are needed to gain the individual’s trust, and thus be able to provide them with health. Conclusion: The vulnerability of the homeless population is evident, and the performance of the street office as a health strategy for this population is of paramount importance, because it is with them that it is possible to interact with the territory and individuals with the sole purpose of make and promote health.